Comparative Transcriptomics During Brown Rot Decay in Three Fungi Reveals Strain-Specific Degradative Strategies and Responses to Wood Acetylation - Kölle, Martina; Crivelente Horta, Maria Augusta; Benz, J. Philipp; Pilgård, Annica (Frontiers in Fungal Biology, 2021)
Brown rot fungi degrade wood in a two-step process in which enzymatic hydrolysis is preceded by an oxidative degradation phase. While a detailed understanding of the molecular processes during brown rot decay is mandatory for being able to better protect wooden products from this type of degradation, the underlying mechanisms are still not fully understood. This is particularly true for wood that has been treated to increase its resistance against rot. In the present study, the two degradation phases were separated to study the impact of wood acetylation on the behavior of three commonly used brown rot fungi. Transcriptomic data from two strains of Rhodonia placenta (FPRL280 and MAD-698) and Gloeophyllum trabeum were recorded to elucidate differences between the respective decay strategies. Clear differences were found between the two decay stages in all fungi. Moreover, strategies varied not only between species but also between the two strains of the same species. The responses to wood acetylation showed that decay is generally delayed and that parts of the process are attenuated. By hierarchical clustering, we could localize several transcription factors within gene clusters that were heavily affected by acetylation, especially in G. trabeum. The results suggest that regulatory circuits evolve rapidly and are probably the major cause behind the different decay strategies as observed even between the two strains of R. placenta. Identifying key genes in these processes can not only help in decay detection and identification of the pathogen, but might also be informative for other fields, such as biopulping.